Model Konstruksi Komunikasi antar Faith Based Organization dalam Meminimalisir Interfaithconflict pada Pelestarian Adat dan Tradisi Budaya Suku Tengger Tosari Pasuruan - Zainul Ahwan; Moh. Edy Marzuki (IAI Darussalam, 2021)
This study aims to find out how the communication construction model between Faith-Based Organizations is carried out by religious leaders (religious leaders) in Minimizing Interfaith Conflict in Preserving Customs and Cultural Traditions of the Tengger Tribe in Tosari, Pasuruan Regency. This study uses the Coordinated Management Of Meaning Theory approach of Barnett Pearce and Vernon Cronen with descriptive qualitative research methods with interpretive - explanatory research approaches. The results of this study indicate that the concept of management, Faith-Based Organization plays the role of Constitutive rules which is played in two communication messages, namely the first communication message inviting harmony in the internal ummah of each religion and secondly the message of peace in the community by being jointly involved in various activities-traditional activities of the Tengger Tribe. In the context of the regulatory rules, the Cultural Strength of the Tengger Tribe becomes the basis for a unifying identity/binding of fellow Tengger Tribe. In the concept of meaning, the Tengger Tribe also has cultural patrons (Cultural Patterns) who teach about their obedience to the teachings of their ancestors, known as the term